Pengaruh Pendekatan Nasabah Dan Pengalaman Nasabah Terhadap Loyalitas Nasabah Pada Bank Muamalat KCP Baturaja - Muhammad Adzmy Nur Yansyah; Hilda Hilda; Fakhrina Fakhrina (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The purpose of this study is to determine the influence, Customer Intimacy and Customer Experience on Customer Loyalty at Bank Muamalat KCP Baturaja.This study used primary data with a quantitative approach. Classical assumption testing techniques, and hypothesis testing using IBM SPSS 26 statistical analysis. The results of this study show that Increasing Customer Intimacy has a postive effect on Customer Loyalty (1,822>1,661), while Customer Experience has a significant positive effect on Customer Loyalty (7,931> 1,661). Increase Customer Bonding, Customer Intimacy and Customer Experience simultaneously (35,448> 3,09).